Exponential smoothing application for predicting demand in a small mugs printig company - Moraes, Francielli Silva; Souza, Bruna Gonçalves de; Enami, Lorena Mazia (Brazilian Journal of Production Engineering, 2023)
Demand forecasting techniques are increasingly used as they enable more assertive decision-making by business management. For this, time series, that is, the set of historical data of organizations, have been used due to the increase in the level of competition between companies, which leads to the need for more efficient and effective data analysis for decision-making. One of these techniques is exponential smoothing, which consists of a simple application of models with weights that decay exponentially over time, usually showing good conformity for stock data. Thus, in this work, the quantitative method of exponential smoothing was analyzed in a stamping of mugs to increase the precision of the forecasts and contribute to the decision-making of managers. The data correspond from July 2019 to October 2021 and were manipulated with the aid of the R software. The multiplicative errors model presented a good fit, and consequently, proved to be usable.
Keywords: Time series; Decision making; Demand